Effect of Hole Diameter and Drying Condition on Shrinkage and Defect of Sugi (Cryptomeria japonica D. Don) Wood in Convective Air Dryer - Yustinus Suranto; Kazuo Hayashi (Wood Research Journal, 2011)
Sugi wood containing pith in the centre of specimen has a very low drying ability and very easy to suffer a defect due to drying on convective dryer. Trunk of sugi trees grown artificially in Matsuyama forest district were cut longitudinally to some rectangular samples in dimension of 12.3 cm x 12.3 cm x 1.5 cm (length). Every six of samples were grouped in one group. The first unit of the sample in every group was intended to measure initial moisture content and another five units of the samples  were subjected to treatment in a hole in the center of the sample with a diameter’s dimension of 0 cm, 2.46 cm, 3.075 cm, 4.1 cm and 6.15 cm respectively. The first until the ninth  group were dried in air convective dryer with temperature of 50°C and relative humidity of 80%, while the tenth until the nineteenth group were dried at temperature of 80°C and relative humidity of 87%. Every stage of drying, each of the samples was weighted and measured for tangential and radial shrinkage as well as length of crack. Data was analyzed using completely randomized design in a factorial arrangement.The result showed that the smaller hole diameter and the higher drying condition, the lower  final moisture content, the higher tangential shrinkage, the higher radial shrinkage and the longer of the total crack.